Analisis Preferensi Visual Lanskap Pesisir Daerah Istimewa Yogyakarta untuk Pengembangan Pariwisata Pesisir Menuju pada Pengelolaan Wilayah Pesisir Berkelanjutan - Khakhim, Nurul; Soedharma, Dedi; Mardiastuti, Ani; Siregar, Vincentius P.; Boer, Mennofatria (Forum Geografi, 2008)
The aim of this research is to analyze of DIY coastal landscape with visual preference analysis for suistanble coastal tourism development and management. The unit of analysis that used is coastal typology. The guideline in deciding the classification of coastal typology is using the Response-Process System with relief/slope, main constructing material, genesis process and dominate process happened in the meantime such as tide, wave and river flow. This response-process system divide the coastal typology into seven classes including coastal typology of land erosion coast, sub aerial deposition coast, volcanic coast, structurally shaped coast, wave erosion coast, marine deposition coast and coast built by organism. The method of SBE (Scenic Beauty Estimation) is used for visual preference analysis, and the method used to compose the policy of costal tourism development is SWOT method. Result shows that all seven coastal typology are found in the coastal area. Land erosion coast and coast built by organism dominate in Gunungkidul coastal area and then in Bantul and Kulon Progo coastal area are dominated by marine deposition coast and sub aerial deposition coast. Volcanic coast, structurally shaped coast, wave erosion coast can only be found in a small area of Gunungkidul coast. Each of this coastal typology has a special land characteristic which can be used to develop its potential. Coast built by organism is very suitable for tourism activity proved by the high score of SBE from the respondents. Recommendation for developing coastal area in area of interest is by developing the coastal natural resources suitable to its physical typology, because this will make the management of coastal area for continuous development easier. Recommendations for coastal management in Gunungkidul including mapping and classification of protected karst area and mineable karst area to secure the run of coastal area management, for coastal management in Bantul using Managed realignment which plans for retreat and adopts engineering solutions that recognise natural processes of adjustment, and identifying a new line of defence where to construct new defences and move seaword model by constructing new defenses seaward the original ones. Last, for Kulon Progo coastal area using hold the line model whereby seawalls are constructed around the coastlines.